2009
DOI: 10.1002/ejoc.200900197
|View full text |Cite
|
Sign up to set email alerts
|

Karplus‐Type Dependence of Vicinal 119Sn‐13C and 119Sn‐1H Spin‐Spin Couplings in Organotin(IV) Derivatives: A DFT Study

Abstract: The empirical Karplus-type dependence of 3 J( 119 Sn, 13 C) and 3 J( 119 Sn, 1 H) couplings in organotin(IV) derivatives has been computationally validated by DFT methods both at the nonrelativistic and scalar ZORA relativistic level. A preliminary calibration of the computational protocols, by comparing experimental and calculated couplings for a set of suitable rigid molecules, revealed their high predictive power: in particular, relativistic results for 3 J( 119 Sn, 13 C) have a mean absolute error of just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
(68 reference statements)
4
12
0
Order By: Relevance
“…[7a] Interestingly, yields were found to be higher when reactions were carried out in benzene instead of cyclohexane which is most likely due to the higher solubility of N ‐protected β‐amino alcohols 2 in such solvent (65 % compared to 45 % for 3a , Table , Entries 1 and 2; and 79 % compared to 61 % for 3c , Table , Entries 4 and 5). The assignment of the trans or cis configuration was unambiguously obtained on the basis of 3 J Sn‐C‐Z‐C , 3 J H‐H , 2 J Sn‐H and δ H2 values for the oxazolidine NMR spectra; these agreed well with our previous work and with theoretical studies reported for the evaluation of 3 J Sn‐C‐Z‐C . Furthermore, these assignments were corroborated by NOESY experiments.…”
Section: Resultssupporting
confidence: 89%
“…[7a] Interestingly, yields were found to be higher when reactions were carried out in benzene instead of cyclohexane which is most likely due to the higher solubility of N ‐protected β‐amino alcohols 2 in such solvent (65 % compared to 45 % for 3a , Table , Entries 1 and 2; and 79 % compared to 61 % for 3c , Table , Entries 4 and 5). The assignment of the trans or cis configuration was unambiguously obtained on the basis of 3 J Sn‐C‐Z‐C , 3 J H‐H , 2 J Sn‐H and δ H2 values for the oxazolidine NMR spectra; these agreed well with our previous work and with theoretical studies reported for the evaluation of 3 J Sn‐C‐Z‐C . Furthermore, these assignments were corroborated by NOESY experiments.…”
Section: Resultssupporting
confidence: 89%
“…The perfect correlation of Sn, 1 H) in organotin(IV) derivatives with dihedral angles described by empirical Karplus-type equations are validated by DFT methods at both the non-relativistic and scalar ZORA relativistic levels. [107] Concerning 3 J( 119 Sn, 13 C) the relativistic protocol gives results which are in excellent agreement with the experimental coupling constants. Furthermore, it has also been reported that the electron-withdrawing strength of the N-substituents strongly affects the magnitude of the couplings and shape of the Karplus-type curve.…”
Section: Dft Calculationssupporting
confidence: 80%
“…12 Recently, we reported on DFT calculations, at the relativistic and nonrelativistic levels, of the vicinal coupling constants for the same set of rigid compounds used by Kitching and Quintard to derive the corresponding Karplus-type equations. 13 The agreement with experimental data was very good. We also highlighted the strong influence of substituents and coupling paths on the value of the coupling constant which is, therefore, not dependent on the dihedral angle j only.…”
Section: Introductionsupporting
confidence: 61%
“…Early works, concerning the validation of Karplus-type equations involving tin in organotin(IV) derivatives, were carried out by Kitching and co-workers for 3 J( 119 Sn-C-C- 13 C), based on experimental couplings observed in a set of rigid polycyclic compounds, 9 and by Quintard and co-workers who derived analogous relationships for vicinal couplings between tin and deuterium, 3 J( 119 Sn-C-C-2 H). 10 This latter equation can be extended to tinproton couplings, 3 J( 119 Sn-C-C-1 H), by a simple conversion.…”
Section: Introductionmentioning
confidence: 99%